Wrocławs Music Therapy Models - Cylulko, Paweł. Redakcja naukowa; Gładyszewska-Cylulko, Joanna. Redakcja naukowa (Wroclawskie modele muzykoterapii, 2016)
The second volume in the “Wrocław Music Therapy” series presents music therapy models developed in Wrocław. It includes articles by authors connected with the Department of Music Therapy at the Karol Lipiński Academy of Music in Wrocław and the Main Board of the Polish Music Therapists’ Association, who have a wealth of experience gained through academic research, therapy, training and organizational activities. We sincerely hope that the publication will significantly contribute to further academic advances in the music therapy field, while bolstering the music therapy profession and presenting the work of the Department of Music Therapy, which has been going on for almost forty-five years
Wrocław Music Therapy, vol. 2
Keywords: cardiac rehabilitation; early school curriculum; music therapy; choreotherapy; neurotic disorders; pediatrics; spontaneous musical theatre technique (STM); surdo music therapy; typhlo music therapy